The effect of price and product quality on purchasing decisions on halal umkm products in medan city - Hartin Nst, Venny Fraya; Ichsan , Reza Nurul (Enrichment : Journal of Management, 2023)
Many people complain, because there are still many food products, especially imports, do not have halal certification, while free halal certification is one of the efforts of the Medan City Government to help MSMEs develop, so it is necessary to conduct research on how much influence price and product quality have on purchasing decisions on MSME Halal Products in Medan City, this research methodology is used in this research is quantitative research. Primary data collection through questionnaires distributed to 60 consumers of MSME Halal products in Medan City. Secondary data will also be used to obtain additional information about MSMEs in Medan City, such as Price, Product Quality and Purchasing Decisions and Halal Products, the results in this study are simultaneously influencing Price and Product Quality on purchasing decisions for halal products at MSMEs in Medan City by 0.444 which means 44.4%, the rest is influenced by other variables from outside the variables studied